2016
DOI: 10.1007/s41133-016-0003-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effect of Audio and Visual Notifications on Workspace Awareness Using Head-Mounted Displays for Remote Collaboration in Augmented Reality

Abstract: In many fields of activity, working in teams is necessary for completing tasks in a proper manner and often requires visual context-related information to be exchanged between team members. In such a collaborative environment, awareness of other people's activity is an important feature of shared-workspace collaboration. We have developed an augmented reality framework for virtual colocation that supports visual communication between two people who are in different physical locations. We address these people a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…3). This design satisfied three requirements from prior work: (1) the notification should reveal information about the drawing interaction by presenting temporal information indicating when annotations are drawn [43], (2) the notification should not require focused attention nor disturb the ongoing primary task [24,48], and (3) the notification should be easily recognized as being noticeable with its size and color [46,47] (i.e. the size of it was much bigger than an annotation as it covered every sides of the screen).…”
Section: Experimental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…3). This design satisfied three requirements from prior work: (1) the notification should reveal information about the drawing interaction by presenting temporal information indicating when annotations are drawn [43], (2) the notification should not require focused attention nor disturb the ongoing primary task [24,48], and (3) the notification should be easily recognized as being noticeable with its size and color [46,47] (i.e. the size of it was much bigger than an annotation as it covered every sides of the screen).…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…Gutwin et al [41,42] explored audio notification when a user watched a video, and found that they were effective. Cidota et al [43] compared an audio notification to a visual notification, and found that participants clearly preferred the visual notification over audio or no notifications. In our second study, we extend Cidota's study [43] investigating visual notification, but focus on the design of the visual notification to notify the local user of the remote user's drawing activity.…”
Section: Awareness and Notificationmentioning
confidence: 99%
“…In the intervening years, SA has become a substantial topic in the general human factors research community with applications as diverse as air traffic control, power systems operation, emergency management and robotic teleoperation for health care, oil and gas exploration, hazardous environments, and mining, among others (see Kedia et al, 2020, Rockwood et al, 2018, and Stanton et al, 2017. SA research has even extended to measure the collaborative performance of teams (Gorman et al, 2006;Salas, et al, 1995) and to guide the design of groupware, such as CMC (Gutwin & Greenberg, 2002) and telepresence (Cidota et al, 2016) systems. With respect to shared situation awareness (SSA) in teams, the SA of the individuals involved is important.…”
Section: Shared Situation Awarenessmentioning
confidence: 99%
“…Earlier research showed that complex tasks with a high search effort can be supported with AR (Reinhart and Patron, 2003 ). With such support, users prefer visual notifications over audio notifications on recent changes in the AR environment (Cidota et al, 2016a , b ). Performing maintenance or repair actions can be faster, more productive and more flexible due to the direct spatial context of the information.…”
Section: Related Workmentioning
confidence: 99%